CT-guided iodine-125 brachytherapy as salvage therapy for local-regional recurrent breast cancer - Wang, Juan; Chang, Xiaojing; Xu, Ke; Liang, Yansong; Zhao, Jinxin; Liu, Zezhou; Zhang, Hongtao (Frontiers in Oncology, 2023)
The treatment of local-regional recurrent Breast cancer (BC) after external beam radiotherapy is challenging. We aim to evaluate the effectiveness and safety of computed tomography (CT)-guided percutaneous iodine-125 brachytherapy for local recurrent BC.We retrospectively analyzed 15 patients with local recurrent BC treated with CT-guided interstitial implantation of iodine-125 seeds. Regular contrastenhanced CT was conducted to evaluate the tumor response. Follow-up survival, quality of life, and adverse events were analyzed.Results: Among the 15 patients, 5 were elderly patients (older than 80 years), and 6 were complicated with chronic underlying diseases. The median number of 125 I seeds implantation was 33 (range 20-130) with median dose 90 (D90, the minimum dose covering 90% of the target volume) of 108 Gy (range, 60-120 Gy). There was no significant difference in D90, V100(the volume of the target receiving 100% of the prescription dose) and V150(the volume of the target receiving 150% of the prescription dose) before and after operation (p >0.05).The median follow-up was 14 months (range, 6-18 months). Six months after operation, the ORR was 66.7% (10/15), and the LCR was 93.3% (14/15). The 6-and 12-month survival rates were 100% and 41.6%, respectively, and the median survival time was 12.5 months.PS score decreased from 1.53±0.81 to 0.53±0.49. The pain score decreased from 2.87±1.67 before operation to 1.07±1.18 after operation, and the differences were statistically significant (p < 0.05). No severe complications occurred.Conclusions: CT-guided iodine-125 brachytherapy provided a safe and effective choice for recurrent BC with significant local therapeutic effects and minor complications, especially for elderly patients with chronic underlying disease and those who were not eligible for surgical resection and had failed to benefit from systemic therapy.